INTERNATIONAL STUDENTS’ADAPTABILITY IN THE CONTEXT OF CROSS-CULTURAL ENVIRONMENT - Khairani, Yulia; Manalu, S. Rouli; Qurrota Ayun, Primada (Interaksi Online, 2024)
The objective of this research is to explain the experience of cross-cultural environment adaptation in international students and what makes international students able to overcome the crisis. The phenomenon of adaptation in a cross-cultural environment is an interesting phenomenon to study because cultural barriers are some of the things that most often cause international students to fail to complete their studies abroad. Many people who are in a new environment face culture shock, which is believed to be a normal condition. However, the level of disturbance experienced by the individual can differ from one person to another. This study uses two concepts, namely u-shaped curve and cross-cultural adaptation theories. The u-shaped curve concept has four stages of adaptation process namely honeymoon phase, crisis, recovery, and adjustment Moreover, the cross-cultural adaptation concept believes that individuals’ capacity for communicating in accordance with new cultural norms and values depends on their ability to change or adapt. It is made up of three crucial elements namely acculturation, deculturation, and assimilation. Each informant is able to be identified with a different process of cross cultural adaptation. There are three findings in this study. First, u-shaped curve theory may not prove for a number of adaptation processes in general. Second, international students undergo different processes of cross-cultural adaptation in cross-cultural environments. Third, what makes international students overcome the crisis include several strategies.